Kontoghiorghes, Erricos John - (:unkn) unknown (My University, 2026)
He taught at the Cass Business School, City University (UK), 1993-1997, at the University of Neuchatel (Switzerland), 1997-2004, and at the University of Cyprus, 2004-2011. He held visiting positions at the University of Rennes 1 (France) and at INRIA-IRISA (France). He holds honorary visiting professorships at the School of Economics and Finance, Queen Mary, University of London and School of Business, Economics and Informatics, Birkbeck, University of London, UK. His work has appeared in a number of international academic journals, including the Journal of Economic Dynamics & Control, Computational Statistics & Data Analysis, Journal of Computational and Graphical Statistics, Parallel Computing, and SIAM Journal on Matrix Analysis and Applications. He has authored and edited books and various special issues of journals on the interface of computing, statistics and econometrics. He is a Co-Editor of the Journal Computational Statistics & Data Analysis (Elsevier) and Associate Editor of the Journal Computational Management Science (Springer).
Keywords: Computational Statistics; Quantitative Methods